Dockyard Road Railway Station - Mumbai Archive Project Team (Jio Institute, 2024)
Dockyard Road opened on November 12, 1925, by carving up a portion of Mazagon Hill. It is a part of the suburban railway network and is under the Harbour Line. The Harbour Line was established on December 10, 1910, when a double line was opened from Kurla to Reay Road, passing through Sewri and Wadala. In 1925, the Harbour Line was connected to Victoria Terminus (CSMT) through an elevated corridor from Reay Road to Sandhurst Road.